Tumor Microenvironment Responsive Single‐Atom Nanozymes for Enhanced Antitumor Therapy. Issue 15 (12th January 2022) - Chang, Mengyu; Hou, Zhiyao; Wang, Man; Li, Chunxia; Al Kheraif, Abdulaziz A.; Lin, Jun
Abstract: Single‐atom nanozymes (SAzymes) with specific response to the unique tumor microenvironment (TME) feature providing 100 % metal atoms utilization for high‐efficient enzyme‐catalyzed therapy and accurate template for the study of therapeutic mechanisms. In this review, we first introduce the various synthetic strategies of SAzymes, and the TME‐responsive SAzymes activities. Next, the TME‐responsive enhanced antitumor therapeutic approaches based on the enzymatic activities of SAzymes are summarized, and the corresponding therapy mechanisms are elaborated. Subsequently, a concise but concentrated summary, and the challenges and opportunities for the future design and engineering of SAzyme are outlined. As a new discipline, SAzymes have vast space for development in enhanced antitumor therapy. This timely review provides guidance and constructive suggestions for the future of SAzymes. Abstract : Single‐atom nanozymes (SAzymes) possess evenly dispersed atomic active centers and well‐defined coordination structure, which provide high enzyme catalytic activity, and clear experimental model for mechanism study. Hence, the enhanced antitumor therapeutic approaches by utilizing tumor microenvironment (TME)‐responsive enzyme activities of SAzymes are revealed. And the corresponding therapeutic mechanisms are also analyzed.